THE INFLUENCE OF CONTENT MARKETING AND KEY OPINION LEADER (KOL'S) ON THE DECISION TO VISIT TRANS ICON MALL SURABAYA - Firsimanda, Ardelia; S.I. Kom., M.I. Kom., Fitri Norhabiba, (The Commercium, 2024)
Digital Marketing has changed the way companies, institutions and other organizations manage business to communicate with their audiences. Apart from products or services, shopping centers or the retail industry also need promotions to get consumers' attention so that their existence can be maintained in a competitive industry. Trans Icon Mall, as a new mall, is aggressively carrying out marketing activities, namely producing marketing content and collaborating with key opinion leaders (KOL's) to expand market share. This research aims to determine the influence of content marketing released by Trans Icon Mall via the Instagram account @transiconmallsurabaya and key opinion leaders (KOL's) on the decision to visit Trans Icon Mall Surabaya. This research is quantitative research using multiple linear regression methods. The results of the F test (Simultaneous) show that Fcount > Ftable or 17.350 > 2.70 with a coefficient of determination (Rsquare) value of 0.534 or 53.4. The magnitude of the influence of content marketing variables and key opinion leaders (KOL's) on visiting decisions is 53.4%. This means that if promotions in the form of marketing content can be packaged well and collaborate with the right key opinion leaders (KOL's), it will influence the audience's decision to visit Trans Icon Mall Surabaya.